Hijab Culture Phenomenon: Between Religion, Trend and Identity - Dewi, Eva; Amrulloh, Muhammad Afif; Suhertina, Suhertina; Sariah, Sariah; Yasnel, Yasnel (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2022)
Hijab (headscarf) as a symbol of religion became phenomenal in the era of development of science and technology nowadays, impacting on the epistemology and axiology of hijab among Muslim women. The style of hijab used by Muslim women both artists and the general public today not only plays with hijab creations, but also clothing that is increasingly diverse, modern and fashionable. Referring the opinion of Nasaruddin Umar, the phenomenon of hijab in Indonesia is currently due to